Retrospective analysis of suspected pesticide-related fatalities admitted to Salt River Mortuary in the West Metropole of Cape Town, Republic of South Africa - Patience, Meryl (Department of Pathology, 2019)
Introduction: Pesticides offer great benefits in the agricultural sector, but exposure may pose both acute and chronic health risks to humans. In developing countries, morbidity and mortality rates related to pesticide exposure are high and in certain areas (such as in rural, lower socioeconomic and/or agricultural-dependent communities), pesticides may be stored in and around homes, which may increase the risk of accidental exposure as well as intentional poisoning. In Cape Town, South Africa, this public health issue is exacerbated by the informal selling of street pesticides. These are pesticides that usually comprise of a mixture of these chemicals, sold unregistered as liquids or granules in bottles or packages without clear identification labels, for domestic use. While cheap and widely available in informal settlements; these pesticide formulations are not regulated and extremely toxic. Data illustrating the extent and nature of fatalities related to acute and chronic pesticide exposure in Cape Town, particularly as related to street pesticides, is limited. This dissertation provides an overview of the literature associated with pesticide toxicity and related mortality, paying particular attention to available South African research. This is followed by a study investigating pesticide deaths at Salt-River Mortuary over a period of five years. Aim: The aim of this study was to determine the prevalence and characteristics of deaths associated with suspected acute pesticide toxicity, to broaden the spectrum of knowledge concerning pesticide-related deaths in Cape Town, South Africa. Methods: A retrospective analysis of cases admitted to Salt River Mortuary (SRM) from 2011 to 2015 (inclusive) was conducted. Demographic, autopsy, investigative and toxicological data (where available) were collected from post-mortem and other investigative reports. Results: Of the total of 16,453 cases admitted to SRM over a five-year period from January 2011 until December 2015, 104 (0.63%) were deemed to be acutely pesticide-related based on available autopsy data. There was an equal number of male (n=52; 50%) and female (n=52; 50%) victims. Most deaths (n=74; 71%) occurred at medical centres following exposure, and Terbufos was found to be the common pesticide detected analytically (n=42, 61%) in toxicology reports available (76%). Results revealed that (60%) of acute pesticide toxicity cases were suspected suicides, while (6%) of cases were suspected accidents and (3%) cases were suspected homicides, while the remainder were still undetermined pending toxicological investigations. Conclusion: A history of ingestion, autopsy findings and toxicological results (if available) assisted in identification of these cases, most of which came from lower socio-economic communities. While the number of overall cases is low, it is evident that these deaths are a public health burden, and may be preventable through improved notification and policy development. Challenges with this study involved the inability to distinguish mortality associated with chronic pesticide exposure, the lack of toxicological results available, limited scene investigation information to identify street pesticide contributions, and that the study was limited to one mortuary in Western Cape. An extension of this research to other mortuaries in Western Cape as well as collaborative work with community and public health sectors on availability and toxicity of street pesticides will assist in strategic intervention methods and policy reform to reduce accidental and suicidal mortality associated with acute pesticide exposure.